Prognostic Value of the Neutrophil–Lymphocyte Ratio for 28-Day Mortality in Hospitalized Pulmonary Tuberculosis - Ali Napiah Nasution; Perwita Sari Sinaga; Sri Wahyuni Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Pulmonary tuberculosis (TB) remains a leading cause of infectious mortality. The neutrophil–lymphocyte ratio (NLR) is an accessible inflammatory index that may stratify short-term risk in hospitalized TB. To examine whether admission NLR predicts 28-day mortality in pulmonary TB. We conducted a retrospective cohort at Royal Prima General Hospital, Medan (1 January 2023–31 December 2024), among adults (18–65 years) admitted with active pulmonary TB. Demographics, TB category, day-1 neutrophil and lymphocyte counts (to derive NLR), and 28-day outcomes were abstracted from medical records. NLR was analyzed as a continuous variable and as a binary variable using a receiver operating characteristic (ROC)-derived cut-off. Group comparisons used t/Mann–Whitney tests as appropriate; prognostic performance was assessed by area under the ROC curve (AUC). The results of the analysis show that NLR has a significant ability to identify patients at risk of death during treatment. This finding has important implications for clinical management, where the use of NLR as a routine biological marker can assist medical personnel in triage and more timely therapeutic decision-making. Therefore, the application of this parameter is expected to help reduce mortality rates through closer monitoring of high-risk patient groups. Keywords: Pulmonary Tuberculosis, Neutrophil–Lymphocyte Ratio, 28-Day Mortality, Prognosis, Biomarkers.